Analysis of erosion susceptibility through urban scenarios for an expanding area - Pascoto, Tamara Vieira; Furegatti, Simone Andrea; Peixoto, Anna Silvia Palcheco (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
Urban scenarios can be used by decision makers on matters related to urban expansion, especially when urban areas have socio-environmental problems, such as those resulting from erosion processes. The aim is the analysis of erosion susceptibility with the construction of urban scenarios using the AHP method to assist decision making on urban expansion. Thus, the AHP (Analytical Hierarchical Process) technique was employed to analyze the data collected and a GIS for the spatialization and building of these scenarios. The methodology was developed based on a real case of a Brazilian city located in the state of São Paulo. To validate the methodology, the current scenario of the studied area was constructed and compared with the actual situation of the place. As a conclusion, the study was validated for the applied area and proved to be a tool capable of assisting local governments regarding decision-making processes for urban expansion. Keywords: Urban Scenarios, AHP, Erosive Processes, Urban expansion, Erosion susceptibility